Pattern of Heart Valve Involvement in Rheumatic Heart Disease - Koju, Rajendra; Gurung, R; Pant, P; Pokharel, B; Bedi, TRS (Nepalese Heart Journal, 2017)
Rheumatic heart disease is the most important consequence of acute rheumatic fever. Both are common cardiovascular problems in Nepal. Echocardiographic detection of rheumatic heart disease is important to establish the diagnosis. The involvement of valves and their severity guides the therapeutic options. A total of 133 valvular heart disease cases attended in Dhulikhel Hospital between July 2008 to June 2009 were analyzed. Fifty-one patients, in whom the problems were rheumatic in origin were studied. Among them, 12% (6) had isolated aortic valve involvement, 35%(18) had isolated mitral valve and 53%(27) ahd mixed involvement. Severe mitral stenosis accounts for 24% of all mitral stenosis and severe aortic stenosis is 20% fo all aortic stenosis. The rates for severe mitral regurgitation and severe aortic regurgitaiton are 30% and 28% respectively. Although the study population has a high number of female patients, the differences in the rates of involvement of aortic or mitral valve in both genders are statistically insignificant. The study, although small, confirms that in this population, females are more commonly affected, that the mitral valve is the most commonly damaged valve and that disease affecting multiple valves is marginally more common than isolated valve disease. The detection of valvular involvement at different stages can guide the therapeutic options.